Development of CTAB modified ternary phase α-Fe2O3-Mn2O3-Mn3O4 nanocomposite as innovative super-adsorbent for Congo red dye adsorption. Issue 1 (February 2021) - Prajapati, Anuj Kumar; Mondal, Monoj Kumar
Abstract: In this study, ternary phase Fe2 O3 -Mn2 O3 -Mn3 O4 (FMM) nanocomposites (NCs) were synthesized via a facile co-precipitation method. The surface of synthesized NCs was modified by cationic CTAB surfactant to increase surface functionality and surface area without any phase change. The existence of the ternary phase in NCs was confirmed by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) techniques. Additionally, characterization techniques such as Fourier transform infrared spectroscopy (FT-IR), Brunauer–Emmett–Teller (BET) surface area analysis, point of zero charge, Field Emission scanning electron microscopy (FE-SEM), and transmission electron microscopy (TEM) were examined for FMM NCs and CTAB modified FMM NCs. The FT-IR and BET surface area analysis confirmed that CTAB modified FMM NCs showed excellent functionality and 19.11% higher surface area than unmodified FMM NCs. Thus, the prepared both NCs were used for congo red (CR) dye adsorption from aqueous solution by varying batch experimental parameters, such as initial pH, contact time and temperature with varying the initial concentration of dye. For kinetic rate analysis, the equilibrium time data were fitted with non-linear form of kinetic models such as pseudo-first-order, second-order, and Elovich model. The equilibrium concentration data were fitted with non-linear equation of Langmuir, Freundlich, and Temkin isotherm models. The maximum adsorption capacity of both NCs increased with increasing temperature; increased from 465.39 to 544.5 mg/g and 627.36–705.84 mg/g for FMM NCs and CTAB modified FMM NCs, respectively, with increasing temperatures from 20 to 40 °C. The thermodynamic parameter studies confirmed that spontaneous adsorption of CR onto both NCs. The adsorption capacity of both NCs was also checked by other anionic and cationic dyes. The effect of co-existing anions on the adsorption capacity of both NCs for CR dye adsorption was also investigated in the present work. The regeneration study of both FMM and CTAB modified FMM NCs were accomplished by NaOH, KOH, ethanol, and double-distilled water; reusability experiments of regenerated NCs were also performed. Graphical Abstract: ga1 Highlights: The ternary phase Fe2 O3 -Mn2 O3 -Mn3 O4 NCs synthesized by co-precipitation method and NCs surface modified by CTAB surfactant. XPS analysis confirmed the existence of ternary phase in Fe2 O3 -Mn2 O3 -Mn3 O4 NCs via metal oxidation states. CTAB surfactant increased the cationic charge density on the NCs surface, which increases the affinity for anionic Congo red. The adsorption capacities of NCs and CTAB modified NCs were 500.64 and 664.30 mg/g, respectively, at 30 °C.